Comparative analysis of different methods of retraction of the left lobe of the liver during laparoscopic sleeve gastrectomy - O. O. Kalashnikov; O. Yu. Usenko; I. M. Todurov; S. V. Kosiukhno (Сучасні медичні технології)
The global obesity epidemic has led to the increasing popularity of bariatric surgeries. Laparoscopic sleeve gastrectomy is currently the most popular bariatric procedure for obesity. Retracting of the left liver lobe during laparoscopic sleeve gastrectomy is important for achieving an optimal surgical field.